PENGARUH KEADILAN DISTRIBUTIF DAN MORALITAS PAJAK TERHADAP KEPATUHAN WAJIB PAJAK DENGAN VARIABEL INTERVENING KEPUASAN WAJIB PAJAK HOTEL DI KOTA MANADO - Paat, Meidy I.; Sondakh, Jullie J.; Budiarso, Novi Swandari (JURNAL RISET AKUNTANSI DAN AUDITING "GOODWILL", 2021)
This study analyzed the effect of variables such as distributive justice, tax morality on taxpayer compliance with taxpayer satisfaction as an intervening variable. This study examined whether a person's morale affects taxpayer compliance in tax paying. The method used in this study was the quantitative method. The sample in this study was hotel taxpayers in Manado City that were registered at the Manado City Revenue Service office. This study used a quantitative method with an associative design that examined the influence among independent variables, are distributive justice, tax morality, and taxpayer satisfaction on the dependent variable, namely hotel taxpayer compliance. The number of samples used as many as 53 hotel taxpayer respondents, collected by distributing questionnaires to each hotel owner or general manager. The test equipment used in this study was Partial Least Square (PLS) using the SmartPLS program.The results of this study indicate that distributive justice, tax morality, and taxpayer satisfaction have a direct positive effect on taxpayer’s compliance. In addition, it is found during this study that the indirect effect through variable mediating produces a positive effect on taxpayers compliance. Therefore, Distribution justice and Tax morality both are making a positive impact on taxpayers compliance mediated through taxpayer’s satisfaction.